2022
DOI: 10.1038/s41598-022-20742-2
|View full text |Cite
|
Sign up to set email alerts
|

Vigor at work mediates the effect of transformational and authentic leadership on engagement

Abstract: Several studies have posited that authentic leadership (AL) and transformational leadership (TFL) imply ethical behaviour that can mitigate tendencies towards low engagement at work. However, there is a lack of studies analysing, for the same sample, the effect of both styles as a job resource and their effects on employees’ engagement as a means of facilitating their work goals and reducing their job demands. This study addresses this shortcoming by analysing the relations of both leadership styles to vigor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
1
1
0
Order By: Relevance
“…Following the JD-R theory [ 28 ] and the suggestions of Xanthopoulou et al [ 42 ]; a job resource, such as AL, can promote a personal and affective resource such as vigor at work and enhance the level of work engagement. This result confirms the hypothesis concerning the complementarity of both constructs [ 46 , 48 ], as work engagement is increased through levels of vigor at work (H1). This result allows us to propose a new perspective in explaining the link between AL and work engagement.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Following the JD-R theory [ 28 ] and the suggestions of Xanthopoulou et al [ 42 ]; a job resource, such as AL, can promote a personal and affective resource such as vigor at work and enhance the level of work engagement. This result confirms the hypothesis concerning the complementarity of both constructs [ 46 , 48 ], as work engagement is increased through levels of vigor at work (H1). This result allows us to propose a new perspective in explaining the link between AL and work engagement.…”
Section: Discussionsupporting
confidence: 87%
“…To date, there is only a small amount of research addressing the combination of vigor at work with work engagement to demonstrate the lack of overlap between the variables or even to acknowledge their various contributions to different work results [ 46 , 47 ]. In fact, this construct differs from work engagement, empirically showing discriminant validity regarding engagement [ 46 ]. Also, Cortés-Denia et al [ 48 ]; in their systematic review, concluded that vigor at work and work engagement are complementary constructs.…”
Section: Introductionmentioning
confidence: 99%